Microstructure and Wear Resistance of TIG Remelted NiCrBSi Thick Coatings - Guo-lu Li; Ya-long Li; Tian-shun Dong; Hai-dou Wang; Xiao-dong Zheng; Xiu-kai Zhou (Advances in Materials Science and Engineering)
The self-fluxing NiCrBSi coatings with 800 μm thickness were prepared on the surface of AISI1045 steel substrate by plasma spraying. And the remelted coating was obtained using by the tungsten inert gas (TIG) arc process. The microstructure, surface roughness, hardness, phase composition, and wear resistance of the sprayed coating and remelted coating were systematically investigated. The results demonstrate that TIG remelted treatment can significantly eliminate the microscopic defects in thick coating and improve its density. The surface roughness (Ra) of the remelted coating is only 18.9% of the sprayed coating. The hardness of the remelted coating is 26.8% higher than that of the sprayed coating. The main phases in the sprayed coating are changed from γ-Ni, Cr7C3, and Cr2B to γ-Ni, Cr23C6, CrB, Ni3B, and Fe3C. The wear mass loss of the remelted coating is only 17.1% of the sprayed coating. Therefore, a Ni-based thick coating with good wear resistance can be obtained by plasma spraying and remelted technique.